2016
DOI: 10.1038/mtna.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Long Noncoding RNAs in the Senescence-accelerated Mouse Prone 8 Brain Using RNA Sequencing

Abstract: Long noncoding RNAs (lncRNAs) may play an important role in Alzheimer's disease (AD) pathogenesis. However, despite considerable research in this area, the comprehensive and systematic understanding of lncRNAs in AD is still limited. The emergence of RNA sequencing provides a predictor and has incomparable advantage compared with other methods, including microarray. In this study, we identified lncRNAs in a 7-month-old mouse brain through deep RNA sequencing using the senescence-accelerated mouse prone 8 (SAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
4
40
0
1
Order By: Relevance
“…Recently, accumulating data demonstrated that non-coding RNAs (ncRNAs) are key regulators in both normal physiological and pathological conditions [5][6][7]. LncRNAs which are defined as those longer than~200 nucleotides, have been extensively characterized and it is evident that they are taking crucial roles in pathologies, including cancers [8][9][10][11][12][13]. In our previous study (GEO, http://www.ncbi.nlm.nih.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulating data demonstrated that non-coding RNAs (ncRNAs) are key regulators in both normal physiological and pathological conditions [5][6][7]. LncRNAs which are defined as those longer than~200 nucleotides, have been extensively characterized and it is evident that they are taking crucial roles in pathologies, including cancers [8][9][10][11][12][13]. In our previous study (GEO, http://www.ncbi.nlm.nih.…”
Section: Introductionmentioning
confidence: 99%
“…5 Long noncoding RNAs (lncRNAs) are a major class of ncRNAs with over 200 nucleotides in length. 6 In recent years, emerging evidence has indicated that lncRNAs can play important roles in cellular and biological functions. They participate in cancer development post-transcriptionally or modulate genes through chromatin regulation.…”
mentioning
confidence: 99%
“…Recent studies have shifted focus to dysregulated gene alterations and regulations in brain aging and related diseases, particularly AD and PD. We have conducted considerable work previously on this aspect, including lncRNA, miRNA, circRNA, and DNA methylation (Zhang et al 2016;. The anomaly of tRFs may exert a great influence on brain aging and related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the expression levels of the tRFs and mRNAs showed significant difference between the SAMP8 and SAMR1 mice and were hence analyzed. Our previous study (Zhang et al 2016) revealed that 482 mRNA transcripts were differentially expressed between SAMP8 and SAMR1 mouse brains at 7 months of age (adjusted p value < 0.05, Supplementary Table S4).…”
Section: Target Predictionmentioning
confidence: 99%
See 1 more Smart Citation